Condylar position in correction of dentofacial deformities - Hase Michael P. (Australasian Orthodontic Journal, 1998)
The mandibular condyles are a reliable reference point for diagnosing soft and hard tissue disharmony of the face and dental structures. Ignoring the seated positron of the condyles may lead to derangements of the joint and relapse of treated malocclusion cases. Muscle releaseis required to record a reproducible condylar positron and a simple technique is described. Once the record is made, meaningful radiograms can be taken to demonstrate the true dentoskeletal deformity. The mounting of dental casts is more accurate if a resilient recording material is used rather than soft wax. This same record should be used when taking cephalometric radiograms to ensure there has been no pivoting of the mandible with luxation of one or both condyles from the fossae. True sagittal and horizontal plane disharmonies can be accurately diagnosed and hence treated if the mandibular condyles are in their seated position when the face and dentition are being evaluated.